Implementasi Metode Demonstrasi untuk Meningkatkan Pemahaman terhadap Konsep Gaya pada Siswa Kelas I Sekolah Dasar - Efrida Hamidah H; Ibnu Muthi (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the effectiveness of the demonstration method in improving the understanding of the concept of force in grade 1 elementary school students. The approach used is a literature study by reviewing various current scientific sources from 2021 to 2025. The results of the study show that the demonstration method is able to transform abstract concepts into concrete experiences that are easy for students to understand. Through demonstrations, students can see firsthand the application of force in everyday life, making it easier to understand. This method also increases students' active involvement, trains observation skills, and supports visual and kinesthetic learning styles. In its implementation, the success of the demonstration method is largely determined by the readiness of the teacher, the use of simple language, a variety of teaching aids, and repetition of activities to strengthen memory. Common obstacles faced include limited tools, time, and teacher skills in designing effective demonstrations. Therefore, school support and collaboration between teachers are key to optimizing the implementation of this method. In conclusion, the demonstration method is an effective learning strategy to improve the understanding of the concept of force, because it is in accordance with the cognitive development stage of early elementary school students who are in the concrete operational phase. Keywords: demonstration method, concept of force, elementary school students, science learning, concrete activities